Digital Islamic Banking Framework for Agricultural Revenue Proficiency - Dr. Haffezullah Talpur, Dr. Haffezullah Talpur; Prof. Dr. Aijaz Ali Khoso, Prof. Dr. Aijaz Ali Khoso; Dr. Muhammad Shoaib Khan Pathan, Dr. Muhammad Shoaib Khan Pathan (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Neediness is a boundless issue in Pakistan, particularly in rustic regions. One reason for this should be the exceptionally separated design of land proprietorship. The Pakistani government has sent off a few projects to lessen pay imbalance in horticulture by making creation motivators, particularly for little ranchers. By and by, the majority of these advantages went to the more affluent landowners who approached the essential extra assets. There are three land change programs in Pakistan intended to increment country livelihoods by expanding farming efficiency and decreasing rustic joblessness. The aftereffect of these changes has never been assessed. No solid examination has yet been completed to gauge its monetary effect. The absence of data makes it very hard for Pakistani lawmakers to form appropriate rural strategy. Along these lines, more nitty gritty data is required on the effect of the above programs on the primary issues in Pakistan.